Origanum majorana as ansiolitic agent in dentistry: a literary review (Research, Society and Development, 2020)
The aim of the present work is to gather the data already acquired about the use of Origanum majorana (manjerona), botanical characteristics, main constituents and scientific studies about the species as a phytotherapeutic agent in dentistry, focusing on potential use as anxiolytic. A literature review was conducted from 2009 to 2019 on the Academic Google and Scientific Electronic Library Online search platforms. The main constituents identified in O. majorana essential oil were terpinen-4-ol, γ-terpinene and α-terpinene. Another important compound of this species would be cis-terpineol, which would have anesthetic activity and the potential to modulate GABAA capacity. Studies conducted with O. majorana essential oils promoted muscle relaxation in the gastropod Pomacea canaliculata at concentrations above 100μL L -1, as well as sedation in the fish species Rhamdia quelen at a concentration of 100 μL L -1, and anesthesia at concentrations of 200, 300, 400 and 500 μL L -1 Marjoram is also attributed to antimicrobial, antioxidant, anesthetic, relaxing and cytotoxic effects. Origanum majorana is a species widely used in the treatment of Central Nervous System disorders due to its antiepileptic and sedative effects. Recent research has shown that the antimicrobial effect is also present, but further studies focusing only on isolated microbial strains are needed. Although their results are proving to be effective, it must be emphasized that natural products can also have adverse effects.